2016
DOI: 10.1080/24701394.2016.1209193
|View full text |Cite
|
Sign up to set email alerts
|

Spatial genetic structure of the cyprinid fish Onychostoma lepturum on Hainan Island

Abstract: Population genetic structure of Onychostoma lepturum on Hainan Island was investigated based on mitochondrial CR + cyt b region in 63 specimens collected from four populations. Population analyses indicated significant genetic structure (F = 0.749) and displayed a significant relationship between phylogeny and geography (N = 0.750 and G = 0.140). Thirty-one mtDNA haplotypes were classified into four lineages, and these lineages had an almost allopatric distribution. The results of a statistical dispersal-vicar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 46 publications
4
20
2
Order By: Relevance
“…3). This result agrees with previous studies (Yang et al 2016; Zhou et al 2017). The WY Range is located in the central and southern regions of Hainan Island and approaches an elevation of 1800 m. The landforms reflect that the rivers on island originate from the central mountainous area and flow outwards.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…3). This result agrees with previous studies (Yang et al 2016; Zhou et al 2017). The WY Range is located in the central and southern regions of Hainan Island and approaches an elevation of 1800 m. The landforms reflect that the rivers on island originate from the central mountainous area and flow outwards.…”
Section: Discussionsupporting
confidence: 94%
“…Due to the steep topology of the island, most rivers run directly into the oceans with no connection to the neighboring drainage systems. As in previous phylogeographic studies of freshwater fishes (Yang et al 2016; Zhou et al 2017), the WY Range was an important barrier. Zhou et al (2017) found that the populations of the cyprinid fish O. lepturum on Hainan Island could be divided into three units based on their location in the Qiongzhou Strait, the Gulf of Tonkin and the South China Sea.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations